Identification of Misconceptions about Substance Pressure in Junior High School Students using the Three-Tier Diagnostic Test - Ahmad Favian Maulana; Lini Fitriya; Nury Najma Layly; Nurul Hidayah Putry; Khansa Alia Faisyah; Manis Ratna Sari Dewi; Fina Amanatillah; Indri Sari Utami (Equator Science Journal, 2025)
This study aims to identify and analyze the misconceptions experienced by junior high school students regarding the material on pressure in substances, understand in depth the misunderstandings that arise among students, and explore the reasons behind these erroneous understandings. Using the Three Tier Test Diagnostic instrument accompanied by CRI, this study seeks to provide a clear picture of students’ level of understanding of the concept of pressure and to develop effective learning strategies to address these misconceptions. The method used is qualitative descriptive, as this study aims to describe the misconceptions experienced by students, understand students’ misconceptions in depth and comprehensively, and explore the reasons behind students’ misunderstandings regarding the material on pressure in substances. This study uses a direct survey method with a sample of 30 ninth-grade students from two different schools. Of the 30 students, 7 were male, and 23 were female. The data collection technique in this study employs three-tier diagnostic tests. The test technique consists of 15 multiple-choice questions accompanied by instructions on how to answer the questions. The results of this study show that 59% of students had misconceptions about pressure, 15% of students understood the concept well, 3% of students did not understand the concept but were unsure, and 23% of students did not know the concept.